THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON COSMETIC REPURCHASE DECISIONS ON SHOPEE WITH CONSUMER SATISFACTION AS AN INTERVENING VARIABLE - Yeyen Deskaryani; Abdul Hadi; Titin Hartini (CV. Cendikiawan Muda Sriwijaya, 2025)
This research starts from the problem of whether product quality and price have a simultaneous and partial effect on the decision to repurchase cosmetics at Shopee with consumer satisfaction as an intervening variable. The aim of this research is to find out and analyze how much influence product quality and price have on the decision to repurchase cosmetics. Then to see and analyze whether consumer satisfaction can mediate product quality and price on consumer satisfaction. The data collection technique is in the form of distributing questionnaires with a Likert scale. The data analysis technique uses quantitative analysis with PLS Algorithm and Bootstrapping analysis using the SmartPLS3 application. The research results show that: 1) Product quality influences repurchase decisions. 2) Product quality influences consumer satisfaction. 3) Price influences repurchase decisions. 4) Price influences consumer satisfaction. 5) Consumer satisfaction influences purchasing decisions. 6) Product quality through consumer satisfaction has a positive effect on repurchase decisions. 7) Price through consumer satisfaction has a positive effect on repurchase decisions. Keywords: Product Quality, Price, Cosmetic Repurchase Decisions, consumer satisfaction